Erlatiboak iparraldean "Haur prodigo"aren 141 itzulpenetan - Hidalgo, Bittor (Anuario del Seminario de Filología Vasca "Julio de Urquijo", 2009)
The article attempts to analyze the comparative usage of the different relative clause types through the 141 translations of the parabola of the Prodigal son in the Bourciez collection. The equivalences of the relative clauses of the original in the Basque translations. The amount of relative clauses in comparison to the original. The distribution of left and right branching relative clauses. That of -(e)n and bait- relatives. And among the right branching relatives, that of zein… relatives, bait- relatives, -(e)n… relatives after an indefinite or a definite nominal head, and among the latter whether there is or there is not case agreement between the nominal head and the relative apposition. Also the occasional use of some modal -(e)la(rik) sentences instead of normal relatives. Always collecting the data territorially and comparing them with the data coming from previous analyses. Emphasizing above all the variability between translators and of each of the translators when using each of the different relative clause types. Also the comparison of the different types of relatives, with the supposed restrictive character of each of them.